The LEFT VENTRICULAR GEOMETRY AMONG CHRONIC KIDNEY DISEASE PATIENTS: THE ROLE OF ANEMIA - AJIBARE, ADEOLA; Oladimeji, Oluwaseye; ODEYEMI, Ayoola; Iyayi, Abisola; Oladimeji, Alaba; Ojo, Olufemi; Adebola, Alaba; Awobusuyi, Jacob; Adekoya, Adebowale (UNUSA Press, 2023)
BACKGROUND: Anaemia and abnormal left ventricular (LV) geometric pattern are common findings in Chronic Kidney disease (CKD) patients. OBJECTIVES: To assess LV geometric pattern and its relationship with anaemia among CKD patients. METHODS: A cross sectional study of 163 subjects (102 and 61 CKD subjects with and without anaemia respectively). Echocardiography determined the LV geometric pattern while packed cell volume (PCV) levels determined anaemia. RESULTS: The mean age of subjects with and without anaemia was 54.04 ± 14.47 and 54.92 ± 15.67 years respectively (p = 0.717) while the prevalence of LVH among the two groups was 68.8% and 57.9% respectively (p = 0.174). The most frequent LV geometry in both groups was concentric LVH (53.8% and 43.9% respectively). Prevalence of LV systolic dysfunction was 45%, higher among anaemic subjects (58(61.7%) vs 10(17.5%)) p < 0.001. There was a strong negative correlation between PCV and left ventricular mass index (r = -0.345, p = 0.001) among anaemic subjects, but weak positive correlation among patients without anaemia (r = 0.001, p = 0.993). CONCLUSION: Anaemic CKD patients had a high prevalence of abnormal LV geometry with significant contribution from anaemia. Early management of anaemia may thus improve cardiovascular outcomes.